EFEKTIVITAS PENGGUNAAN MEDIA BERBASIS APLIKASI SMART SPLIT PADA PEMBELAJARAN MATEMATIKA - Dukei, Nurain; Katili, Sukri; Aries, Nur Sakinah; Arif, Rifda Mardian; Pulukadang, Wiwy Trianty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The objective of this study is to develop a Smart Split application-based media that meets the criteria of feasibility, practicality, and effectiveness in mathematics learning to improve student learning outcomes on the topics of equivalent fractions and comparing fractions in Grade IV at SDN 16 Telaga Biru, Gorontalo Regency. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages analyze, design, develop, implement, and evaluate. The feasibility of the Smart Split application-based media was tested through validation by a team of experts. The validation results showed an average percentage score of 93%, categorized as highly feasible for use by teachers and students in elementary schools. To test practicality, the researcher used teacher observation sheets and student response sheets, which resulted in scores of 98.75% and 91.67%, respectively, both classified as highly practical. Regarding media effectiveness, the media implementation in Grade IV at SDN 16 Telaga Biru was measured using pre-tests and post-tests. The results showed that the average pre-test score of 30 increased to 85 33 in the post-test. The N-Gain score was 0.78, which falls into the